2002
DOI: 10.1037/1089-2699.6.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Role ambiguity, role efficacy, and role performance: Multidimensional and mediational relationships within interdependent sport teams.

Abstract: Male secondary school rugby players (N ϭ 271) participated in a study examining role ambiguity, role efficacy, and role performance. A multidimensional measure was used to assess 4 manifestations of role ambiguity in offensive and defensive contexts. Multiple role ambiguity dimensions explained variance in efficacy and performance. Consistent with theorizing by A. Bandura (1997) and R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
156
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 32 publications
10
156
2
2
Order By: Relevance
“…The findings also support previous research by Beauchamp et al (2005), who found that clarity about the scope of responsibility was positively associated with role satisfaction. In addition, Beauchamp et al (2002) reported that when athletes were unclear about their scope of responsibilities, they were less able to act appropriately insofar as their role performance was impaired.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings also support previous research by Beauchamp et al (2005), who found that clarity about the scope of responsibility was positively associated with role satisfaction. In addition, Beauchamp et al (2002) reported that when athletes were unclear about their scope of responsibilities, they were less able to act appropriately insofar as their role performance was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…While the RAS scale of Beauchamp et al (2002) measures role ambiguity explicitly in relation to offensive and defensive roles, in the current study, the RAS was modified to remove differentiation between offensive and defensive roles and instead sought to measure role ambiguity per se. Handball as a sport is becoming faster and players at a high level must always have an overview of the way the game is being played.…”
Section: Role Ambiguity (Ra) and Role Satisfaction (Rs) Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations